Carbon monoxide decreases endosome–lysosome fusion and inhibits soluble antigen presentation by dendritic cells to T cells. Issue 11 (21st August 2013) - Tardif, Virginie; Riquelme, Sebastián A.; Remy, Séverine; Carreño, Leandro J.; Cortés, Claudia M.; Simon, Thomas; Hill, Marcelo; Louvet, Cédric; Riedel, Claudia A.; Blancou, Philippe; Bach, Jean‐Marie; Chauveau, Christine; et al.
<x xml:space="preserve">Abstract</x> Heme oxygenase‐1 (HO‐1) inhibits immune responses and inflammatory reactions via the catabolism of heme into carbon monoxide (CO), Fe2+, and biliverdin. We have previously shown that either induction of HO‐1 or treatment with exogenous CO inhibits LPS‐induced maturation of dendritic cells (DCs) and protects in vivo and in vitro antigen‐specific inflammation. Here, we evaluated the capacity of HO‐1 and CO to regulate antigen presentation on MHC class I and MHC class II molecules by LPS‐treated DCs. We observed that HO‐1 and CO treatment significantly inhibited the capacity of DCs to present soluble antigens to T cells. Inhibition was restricted to soluble OVA protein, as no inhibition was observed for antigenic OVA‐derived peptides, bead‐bound OVA protein, or OVA as an endogenous antigen. Inhibition of soluble antigen presentation was not due to reduced antigen uptake by DCs, as endocytosis remained functional after HO‐1 induction and CO treatment. On the contrary, CO significantly reduced the efficiency of fusion between late endosomes and lysosomes and not by phagosomes and lysosomes. These data suggest that HO‐1 and CO can inhibit the ability of LPS‐treated DCs to present exogenous soluble antigens to naïve T cells by blocking antigen trafficking at the level of late endosome–lysosome fusion.